Effects of Buoyancy and Season on Turion Dispersal of Submerged Macrophyte Potamogeton crispus L. Issue 3 (30th June 2014) - Xie, Dong; Zhou, Hengjie; Ji, Haiting; Chen, Yushun; An, Shuqing
<x xml:space="preserve">Abstract</x> Propagules dispersal and colonization ability are major issues of macrophyte regeneration. For submerged macrophyte Potamogeton crispus L., turion dispersal along water flow can favor the long‐distance expansion of its population; therefore, it is crucial to investigate factors that affect turion dispersal. For this purpose, we studied effects of buoyancy and season on dispersal P. crispus turions by collecting field samples from Taihu Lake, over a three‐months period (turion‐formatting season, from May to July). Germination experiments (30 days in each sampling month) revealed that the floating turions germinated earlier and faster than the sinking ones across the three sampling months. After germination, the floating turions showed higher seedling height; whereas the sinking turions accumulated more sprouts biomass. The soluble sugar, total nitrogen (TN), and total phosphorus (TP) concentrations were found higher in the floating turions. The starch concentrations remained high without buoyancy or season effects. These results indicate that both internal (e.g., buoyancy, soluble sugar, TN, and TP concentrations) and external environmental factors (e.g., light condition and temperature) may contribute to germinability and plant growth of P. crispus turions. This study offers new insights into the dispersal of asexual propagules of submerged macrophytes.